Comment La charte “Ya d’ar brezhoneg” est devenue un outil incontournable de la revitalisation et de la normalisation de la langue bretonne - Cédric Choplin (Lengas)
Initiated and promoted by the Office de la langue bretonne (now the Public office for the Breton language), the Ya d'ar Brezhoneg (Yes to Breton) charter has become, after twenty years of existence, an essential tool for the revitalisation and standardisation of the Breton language. With no less than 790 private structures, 231 municipalities and 15 inter-municipal structures as signatories, it benefits from publicity and a certain impact in all sectors of life in the region. How was this charter conceived and how did it become so successful, what are the limits of its actions today, and what are the perspectives?In this article, which is largely based on interviews with various actors and a study of the press, we will first focus on the sociolinguistic reflection that presided over the design of the charter; secondly, we will discuss the keys to its success and the rare negative reactions it has provoked; thirdly, we will return to the experience of the entrepreneur Denez Pichon, a signatory of the charter in his high-tech company.